First, note that L(ambda) <> 0 since that would the 4th equation impossible.

I'll get you started and see if you can finish. Re-arrange each equation:

1) yz = L(y+z)

2) xz = L(x+z)

3) xy = L(x+y)

Now take (1) divided by (2) and see if you can get a relationship between x and y. If you can, that will tell you how to get a relationship between x and z. The rest will tumble down. Let me know how you make out.

First, note that L(ambda) <> 0 since that would the 4th equation impossible.

I'll get you started and see if you can finish. Re-arrange each equation:

1) yz = L(y+z)

2) xz = L(x+z)

3) xy = L(x+y)

Now take (1) divided by (2) and see if you can get a relationship between x and y. If you can, that will tell you how to get a relationship between x and z. The rest will tumble down. Let me know how you make out.